Internalization of Freedom to Learn Value in Productive Learning in Vocational Education during the COVID-19 Pandemic - Puji Hastutiningsih; Markhamah Markhamah (Teknodika, 2022)
This study aims to describe the internalization of the value of freedom to learn in learning at SMK N 9 Surakarta. In this case, the data development on COVID-19 figures and government policies in responding to the COVID-19 pandemic by not allowing face-to-face learning requires learning to be carried out using a distance learning model that necessitates teachers to internalize the value of freedom to learn in learning, which is considered to affect the achievement of student competencies. Internalization of the value of freedom to learn can then have a positive and negative effect on learning. For this reason, this study used a qualitative approach, with data collection techniques in the form of interviews, observation, and documentation studies. In this study, there were two points of view on internalization: the basic idea of internalization that adheres to the normative aspect, i.e., laws and circulars from the education office, and several teacher opinions on the freedom to learn policy, i.e., the value of flexibility contained in it. The research results also revealed that the internalization of the value of freedom to learn could facilitate the distance learning process and improve the accomplishmentof student competencies and achievements.